The level of investigations in the image of the hero in artwork (Journal of Philosophy Culture and Political Science, 2016)
In the article is considered the artwork. The artistic culture basis on art. Social dynamics of aesthetics, artistic values are determined through them. Art is the result of artistic images, the ultimate idea derived aesthetic aspects of material and spiritual life. Art is complex configuration and dynamics of culture. As a special branch of human activity art is determined by the original author’s approach.
Keywords: culture; artwork; art; personality; theatre